2011
DOI: 10.1063/1.3549593
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of liquid CO2 for pressures up to 1 TPa

Abstract: We report on the use of first-principles molecular dynamics calculations to examine properties of liquid carbon dioxide in the pressure-temperature range of 0-1 TPa and 200-100 000 K. The computed equations of state points are used to predict a series of shock Hugoniots with initial starting conditions that are relevant to existing and ongoing shock-wave experiments. A comparison with published measurements up to 70 GPa shows excellent agreement. We find that the liquid undergoes a gradual phase transition alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…The trajectory for each of these simulations was used to determine the atomic coordination of C atoms. Here we use the terminology employed in previous studies [23,24] to define the carbon coordination as the number of oxygen and carbon atoms within a specified radial cut-off distance of a given carbon atom. The cut-off distance used for coordination determination was the first minimum of the C O pair correlation function, see for example Boates et al [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trajectory for each of these simulations was used to determine the atomic coordination of C atoms. Here we use the terminology employed in previous studies [23,24] to define the carbon coordination as the number of oxygen and carbon atoms within a specified radial cut-off distance of a given carbon atom. The cut-off distance used for coordination determination was the first minimum of the C O pair correlation function, see for example Boates et al [23].…”
Section: Methodsmentioning
confidence: 99%
“…All simulations were performed with periodic boundary conditions and temperatures were kept constant by a Nosé-Hoover thermostat [21,22] are converged with 32 molecules (96 atoms) in the simulation cell [23,24]. Hence we used a 3 × 3 × 3 body centered cubic supercell of 54 CO molecules (108 atoms) to mitigate finite size effects.…”
Section: Methodsmentioning
confidence: 99%
“…In the theoretical study of Boates et al [2011], solid CO 2 was found to transform from an insulator to a metallic phase at the liquid-liquid transition at 42.2 GPa and 4000 K. It was suggested that metallization is related to the dissociation of CO 2 molecules and the formation of C-C bonds. This hypothesis arose from the observation that there is an apparent correlation between increasing DC conductivity and the number of the C-C species.…”
Section: Metallizationmentioning
confidence: 99%
“…These extreme conditions are significant obstacles that challenge both experimental and theoretical investigations. From first-principles molecular dynamics (MD) calculations, Boates et al [2011] found a liquid-liquid phase transition at 42.2 GPa and 4000 K with the dissociation of carbon dioxide molecules into a variety of molecular species including polymer structures C-C, C-O, and molecular O 2 . A potentially important prediction from that study is that the conductivity of the dissociated liquid is similar to a metal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation